Angiotensin-I converting enzyme (ACE) inhibitory and anti-oxidant activities of sea cucumber (Actinopyga lecanora) hydrolysates - Ghanbari, Raheleh; Zarei, Mohammad; Ebrahimpour, Afshin; Abdul Hamid, Azizah; Ismail, Amin; Saari, Nazamid (MDPI, 2015)
In recent years, food protein-derived hydrolysates have received considerable attention because of their numerous health benefits. Amongst the hydrolysates, those with anti-hypertensive and anti-oxidative activities are receiving special attention as both activities can play significant roles in preventing cardiovascular diseases. The present study investigated the angiotensin-I converting enzyme (ACE) inhibitory and anti-oxidative activities of Actinopyga lecanora (A. lecanora) hydrolysates, which had been prepared by alcalase, papain, bromelain, flavourzyme, pepsin, and trypsin under their optimum conditions. The alcalase hydrolysate showed the highest ACE inhibitory activity (69.8%) after 8 h of hydrolysis while the highest anti-oxidative activities measured by 2,2-diphenyl 1-1-picrylhydrazyl radical scavenging (DPPH) (56.00%) and ferrous ion-chelating (FIC) (59.00%) methods were exhibited after 24 h and 8 h of hydrolysis, respectively. The ACE-inhibitory and anti-oxidative activities displayed dose-dependent trends, and increased with increasing protein hydrolysate concentrations. Moreover, strong positive correlations between angiotensin-I converting enzyme (ACE) inhibitory and anti-oxidative activities were also observed. This study indicates that A. lecanora hydrolysate can be exploited as a source of functional food owing to its anti-oxidant as well as anti-hypertension functions.